Mass administration of azithromycin and Streptococcus pneumoniae carriage: cross-sectional surveys in the Gambia - Sarah E Burr; Sally Milne; James Jafali; Ebrima Bojang; Megha Rajasekhar; John Hart; Emma M Harding-Esch; Martin J Holland; David CW Mabey; Ansumana Sillah; Robin L Bailey; Anna Roca
Objective To evaluate the effect of repeated mass drug administration (MDA) of azithromycin in the Gambia on the nasopharyngeal carriage of Streptococcus pneumoniae and on the emergence of antibiotic-resistant strains. Methods This study involved villages that participated in a cluster randomized trial comparing the effect of one versus three azithromycin MDA rounds on the prevalence of trachoma. Only villages in which most children received 7-valent pneumococcal conjugate vaccine were included. Three cross-sectional surveys were performed in two villages that received three annual MDA rounds: the first immediately before the third MDA round and the second and third, 1 and 6 months, respectively, after the third MDA round. The third survey also covered six villages that had received one MDA round 30 months previously. Pneumococcal carriage was assessed using nasopharyngeal swabs and azithromycin resistance was detected using the Etest. Findings The prevalence of pneumococcal carriage decreased from 43.4% to 19.2% between the first and second surveys (P < 0.001) but rebounded by the third survey (45.8%; P = 0.591). Being a carrier at the first survey was a risk factor for being a carrier at the second (odds ratio: 3.71; P <  0.001). At the third survey, the prevalence of carriage was similar after one and three MDA rounds (50.3% versus 45.8%, respectively; P = 0.170), as was the prevalence of azithromycin resistance (0.3% versus 0.9%, respectively; P = 0.340). Conclusion Three azithromycin MDA rounds did not increase the prevalence of nasopharyngeal carriage of azithromycin-resistant S. pneumoniae strains compared with one round.